Association of a functional RAD52 genetic variant locating in a miRNA binding site with risk of HBV‐related hepatocellular carcinoma. Issue 9 (11th April 2014) - Li, Ziqiang; Guo, Yuan; Zhou, Liqing; Ge, Yunxia; Wei, Lili; Li, Lichao; Zhou, Changchun; Wei, Jinyu; Yuan, Qipeng; Li, Jie; Yang, Ming
<x xml:space="preserve">Abstract</x> As an important member in homologous recombination repair, RAD52 plays a crucial part in maintaining genomic stability and prevent carcinogenesis. Several cancer susceptibility RAD52 single nucleotide polymorphisms (SNPs) have been identified previously. However, little or nothing has been known about the RAD52 SNPs and their functional significance in hepatitis B viruses (HBV)‐related hepatocellular carcinoma (HCC). Therefore, we investigated the association between five RAD52 SNPs (rs1051669, rs10774474, rs11571378, rs7963551, and rs6489769) and HBV‐related HCC risk as well as its biological function in vivo. Genotypes were determined in two independent case–control sets from two regions of China. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated by logistic regression. The allele‐specific regulation on RAD52 expression by the functional genetic variant was examined with normal liver tissues. We found that only the RAD52 rs7963551 SNP was significantly associated with HCC risk, with the odds of having the rs7963551 CC genotype in patients was 0.59 (95% CI = 0.45–0.78, P = 1.5 × 10−4, HCC cases versus chronic HBV carriers) or 0.65 (95% CI = 0.52–0.81, P = 1.1 × 10−4, HCC cases versus healthy controls) compared with the AA genotype. In the genotype–phenotype correlation analyses of 44 human liver tissue samples, rs7963551 CC or AC was associated with a statistically significant increase of RAD52 mRNA expression, which are consistent to functional relevance of allelic regulation of RAD52 expression by rs7963551 SNP and miRNA let‐7 in cancer cells. Our data demonstrated that RAD52 functional rs7963551 SNP contributes to susceptibility to developing HCC. © 2014 Wiley Periodicals, Inc.